2021
DOI: 10.1111/dth.14993
|View full text |Cite
|
Sign up to set email alerts
|

Ixekizumab improves disease severity, clinical symptoms and quality of life in patients with genital psoriasis: A 24‐week real‐life experience

Abstract: Genital psoriasis (GenPs) has been traditionally considered a difficult to treat psoriasis area. Ixekizumab was the first biologic agent demonstrating efficacy and safety in a formal clinical trial on GenPs; however, real-life experiences are limited. To assess real-life effectiveness and safety of ixekizumab in the treatment of GenPs in a case series of patients with moderate-to-severe plaque psoriasis. Adult patients with moderate-to-severe plaque psoriasis involving the genital area received subcutaneous ix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Clinical trials also showed ixekizumab efficacy in long term evaluation, and in the treatment of difficult to treat psoriasis like nails, scalp, palmoplantar, genital, and pustular psoriasis 47–51 . Promising trials' results were evaluated also by real life setting studies, which confirmed trials results and showed interesting results reached with ixekizumab treatment also in terms of PASI90 and PASI100 responses 31,52 . Furthermore, real life studies compared ixekizumab with secukinumab are both highly effective in short‐ and long‐term treatment of psoriasis, even though few differences exist concerning speed of action and long‐term effectiveness, with a faster response in term of achieving PASI75 and PASI90 for ixekizumab 54,55 .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Clinical trials also showed ixekizumab efficacy in long term evaluation, and in the treatment of difficult to treat psoriasis like nails, scalp, palmoplantar, genital, and pustular psoriasis 47–51 . Promising trials' results were evaluated also by real life setting studies, which confirmed trials results and showed interesting results reached with ixekizumab treatment also in terms of PASI90 and PASI100 responses 31,52 . Furthermore, real life studies compared ixekizumab with secukinumab are both highly effective in short‐ and long‐term treatment of psoriasis, even though few differences exist concerning speed of action and long‐term effectiveness, with a faster response in term of achieving PASI75 and PASI90 for ixekizumab 54,55 .…”
Section: Discussionmentioning
confidence: 70%
“…[47][48][49][50][51] Promising trials' results were evaluated also by real life setting studies, which confirmed trials results and showed interesting results reached with ixekizumab treatment also in terms of PASI90 and PASI100 responses. 31,52 Furthermore, real life studies compared ixekizumab with secukinumab are both highly effective in short-and long-term treatment of psoriasis, even though few differences exist concerning speed of action and long-term effectiveness, with a faster response in term of achieving PASI75 and PASI90 for ixekizumab. 54,55 Brodalumab efficacy and safety profiles were evaluated in three randomized double blinded controlled trials (AMAGINE-1, AMAGINE-2 and AMAGINE-3).…”
Section: Discussionmentioning
confidence: 99%
“…Data collection and handling complied with applicable laws, regulations and guidance regarding patient protection, including patient privacy. D. Orsini 1 P. Frascione 2 C. Assorgi 3 A. Pacifico 1 I. Sperduti 4 L. Gargiulo 5,6 L. Ibba 5,6 M. Valenti 5,6 A. Costanzo 4,5 A. Narcisi…”
Section: Data Ava I L a Bi L I T Y S Tat E M E N Tmentioning
confidence: 99%
“…2 Genitals are considered a difficult-to-treat area. 4,5 Topical treatments remain the first-line choice for mild-to-moderate disease. 5 However, corticosteroids are associated with longterm adverse events, and specific data on immunomodulators or vitamin D derivatives are scant.…”
mentioning
confidence: 99%
See 1 more Smart Citation